Hollow Co0.85Se nanowire array on carbon fiber paper for high rate pseudocapacitor - Banerjee, Abhik; Bhatnagar, Sumit; Upadhyay, Kush Kumar; Yadav, Prasad; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2014)
A supercapacitor electrode is fabricated with Co0.85Se hollow nanowires (HNW) array, which is synthesized by wet chemical hydrothermal selenization of initially grown cobalt hydroxyl carbonate nanowires on conductive CFP. The dense self-organized morphology of Co0.85Se HNWs is revealed by scanning/transmission electron microscopy. The as-synthesized Co0.85Se HNWs possess high pseudocapacitive property with high capacitance retention and high durability. The areal capacitance value is seen to vary from 929.5 to 600 mF cm(-2) (60% retention) as the current density is increased from 1 to 15 mA cm(-2), an increase of a factor of 15. Based on mass loading, this corresponds to a very high gravimetric capacitance of 674 (for 2 mA cm(-2) or 1.48 Ag-1) and 444 Fg(1-) (for 15 mA cm(-2) or 11 A g(-1)) in a full-cell configuration with the Co0.85Se HNWs as cathode and activated carbon as anode (asymmetric configuration) promising results are obtained.
Keywords: asymmetric supercapacitor; carbon fiber paper; cobalt selenide; hydrothermal; pseudocapacitor; selenization

MOF-derived crumpled-sheet-assembled perforated carbon cuboids as highly effective cathode active materials for ultra-high energy density Li-ion hybrid electrochemical capacitors (Li-HECs) - Banerjee, Abhik; Upadhyay, Kush Kumar; Puthusseri, Dhanya; Aravindan, Vanchiappan; Madhavi, Srinivasan; Ogale, Satishchandra (Nanoscale, 2014)
Lithium ion hybrid capacitors (Li-HECs) have attracted significant attention for use in next generation advanced energy storage technologies to satisfy the demand of both high power density as well as energy density. Herein we demonstrate the use of very high surface area 3D carbon cuboids synthesized from a metal-organic framework (MOF) as a cathode material with Li4Ti5O12 as the anode for high performance Li-HECs. The energy density of the cell is similar to 65 W h kg(-1) which is significantly higher than that achievable with commercially available activated carbon (similar to 36 W h kg(-1)) and a symmetric supercapacitor based on the same MOF-derived carbon (MOF-DC similar to 20 W h kg(-1)). The MOF-DC/Li4Ti5O12 Li-HEC assembly also shows good cyclic performance with similar to 82% of the initial value (similar to 25 W h kg(-1)) retained after 10 000 galvanostatic cycles under high rate cyclic conditions. This result clearly indicates that MOF-DC is a very promising candidate for future P-HEVs in a Li-HEC configuration.

Nickel cobalt sulfide nanoneedle array as an effective alternative to pt as a counter electrode in dye sensitized solar cells - Banerjee, Abhik; Upadhyay, Kush Kumar; Bhatnagar, Sumit; Tathavadekar, Mukta; Bansode, Umesh P.; Agarkar, Shruti A.; Ogale, Satishchandra B. (RSC Advances, 2014)
Self supported nickel cobalt sulfide (NCS) nanoneedles are directly formed on FTO glass substrates by sulphurization of nickel cobalt oxide nanoneedles (grown by a hydrothermal method) in the presence of a hydrogen sulfide and argon gas mixture. These NCS nanoneedles when used as a counter electrode for dye sensitized solar cells (DSSCs) show efficient catalytic activity towards the I-/I-3(-) redox couple, and lead to an impressive efficiency of 6.9%, compared with 7.7% obtained with a Pt electrode in similarly constructed devices.

Surfactant free gram scale synthesis of mesoporous Ni(OH)(2)-r-GO nanocomposite for high rate pseudocapacitor application - Singh, Upendra; Banerjee, Abhik; Mhamane, Dattakumar; Suryawanshi, Anil; Upadhyay, Kush Kumar; Ogale, Satishchandra (RSC Advances, 2014)
We report a single-step surfactant-free gram scale hydrothermal synthesis of mesoporous Ni(OH)(2) nanoparticles and the Ni(OH)(2)-reduced graphene oxide (Ni(OH)(2)-r-GO) nanocomposite. Interesting morphological features are noted. These nanomaterials are examined and compared as cathode materials for pseudo-capacitor application through detailed characterizations. A high specific capacitance (C-s) of 1538 F g(-1) is observed for Ni(OH)(2)-r-GO even at a high current density of 40 A g(-1), whereas at the same current rate, bare Ni(OH)(2) shows C-s of only 936 F g(-1).